2020
DOI: 10.4196/kjpp.2020.24.3.233
|View full text |Cite
|
Sign up to set email alerts
|

ATG5 knockout promotes paclitaxel sensitivity in drug-resistant cells via induction of necrotic cell death

Abstract: Autophagy regulators are often effective as potential cancer therapeutic agents. Here, we investigated paclitaxel sensitivity in cells with knockout (KO) of ATG5 gene. The ATG5 KO in multidrug resistant v-Ha-ras-transformed NIH 3T3 cells (Ras-NIH 3T3/Mdr) was generated using the CRISPR/Cas9 technology. The qPCR and LC3 immunoblot confirmed knockout of the gene and protein of ATG5, respectively. The ATG5 KO restored the sensitivity of Ras-NIH 3T3/Mdr cells to paclitaxel. Interestingly, ATG5 overexpression resto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Recently, ATG5 has been found to be implicated in doxorubicin resistance in gall bladder cancer [523]. It has been shown that knocking down ATG5 in paclitaxel-resistant cells causes a G2/M arrest and makes cells susceptible to paclitaxel-induced necrosis [524]. Another study showed that direct knockdown of ATG5 increased paclitaxel resistance in Ras-NIH 3T3 (v-Ha-ras-transformed NIH 3T3) cells by reducing the frequency of early apoptotic cells [525].…”
Section: Autophagy Acts As a Chemotherapy Resistance Machinery In The...mentioning
confidence: 99%
“…Recently, ATG5 has been found to be implicated in doxorubicin resistance in gall bladder cancer [523]. It has been shown that knocking down ATG5 in paclitaxel-resistant cells causes a G2/M arrest and makes cells susceptible to paclitaxel-induced necrosis [524]. Another study showed that direct knockdown of ATG5 increased paclitaxel resistance in Ras-NIH 3T3 (v-Ha-ras-transformed NIH 3T3) cells by reducing the frequency of early apoptotic cells [525].…”
Section: Autophagy Acts As a Chemotherapy Resistance Machinery In The...mentioning
confidence: 99%
“…These data suggest that the difference in PTX sensitivity between ATG5 KO and their parental cells may result from the disparity in the proportions of necrotic cells in both populations. Thus, these results demonstrate that the ATG5 KO in multidrug-resistant cells leads to a marked G2/M arrest and sensitizes cells to PTX-induced necrosis [106].…”
Section: Nonapoptotic Forms Of Cell Death Induced By Taxanesmentioning
confidence: 51%
“…Then, the vector was transfected into PC12 cells using Lipofectamine 3000 transfection reagent (L3000075, Thermo), and stable expression cells were screened using 800 μg/ml G418 (G8160, Solarbio). The NLRC3 knockdown vector was constructed according to a previous study [13]. Pairs of oligos were obtained using the following primers: Forward: 5'-CACCGTCAGACTTCTGTTGACCAAG-3', Reverse: 5'-AACCTTGGTCAACAGAAGTCTGAC-3', and oligos were incubated with T4 PNK (M0201S, NEB) at 37°C for 30 min and 95°C for 5 min.…”
Section: Vector Constructionmentioning
confidence: 99%